Real-time assessment of kidney allografts during HOPE using flavin mononucleotide (FMN) — a preclinical study - Sousa Da Silva, Richard X.; Darius, Tom; Mancina, Leandro; Eden, Janina; Wernlé, Kendra; Ghoneima, Ahmed S.; Barlow, Adam D.; Clavien, Pierre-Alain; Dutkowski, Philipp; Kron, Philipp (Frontiers in Transplantation, 2023)
Introduction The gap between available donor grafts and patients on the waiting lists is constantly growing. This leads to an increased utilization of high-risk and therefore more vulnerable kidney grafts. The use of high-risk organs requires further optimization of machine preservation and assessment strategies before transplantation. Hypothermic machine perfusion (HMP) is the standard of care for kidneys originating from donation after circulatory death (DCD), whereas the evidence of HMP with additional oxygen (HOPE) is still very limited. Furthermore, an objective quality assessment of HMP-perfused kidneys is lacking. Recently, the release of mitochondria derived fragments, i.e., flavin mononucleotide (FMN) of complex I during machine liver perfusion was shown to be predictive for liver graft function before implantation. Therefore, the aim of this study was to evaluate, if FMN is useful also for assessment of kidney injury before use. Methods A porcine perfusion model was used to investigate the feasibility of assessment of kidney grafts during hypothermic oxygenated perfusion (HOPE) with either 0, 30 or 60 minutes of warm ischemia. The model with warm ischemia times (WIT) of 30 min and 60 min, was used to mimic a clinically relevant scenario. A group with no warm ischemia time (0′ WIT) served as control group. The groups underwent minimal static cold storage (SCS) of 2 h followed by 2 h of end-ischemic HOPE with repeated real-time FMN measurements. In a further step, these values were related to the release of damage-associated molecular patterns (DAMPs) and to the functionality of the respiratory chain, represented by the capacity of ATP production. Results We demonstrate, first, feasibility of perfusate FMN measurements in perfused kidneys, and secondly its correlation with donor warm ischemia time. Accordingly, FMN measurement showed significantly higher release in the 60-minute WIT group (n = 4) compared to the 30-minute WIT (n = 4) and the control group (n = 4). FMN release correlated also with DAMP signaling, such as the release of 8-OHdG and HMGB1. Finally, ATP replenishment proved to be best in control kidneys, followed by kidneys with 30 min and then by kidneys with 60 min of WIT. Discussion This study demonstrates the feasibility of FMN measurement in kidneys during HOPE. In addition, we show a correlation between FMN quantification and pre-existing kidney graft injury. Based on this, real-time FMN measurement during HOPE may be an objective assessment tool to accept high-risk kidneys for transplantation while minimizing post-transplant dysfunction, moving away from former “gut feeling” towards objective criteria in accepting marginal kidney grafts for transplantation. Graft evaluation based on these results may close the gap between available grafts and patients on the waiting lists by increasing utilization rates without significant impact for the recipients.